Behaviour prediction of glued laminated timber beam made of different hardwood laminations using transformed section method - Gan, Chiew Leng (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2006